PELATIHAN PENERAPAN BLENDED LEARNING MENGGUNAKAN MODEL FLIPPED CLASSROOM DI MAN 1 KAMPAR PADA ERA NEW NORMAL - Molli Wahyuni; Adityawarman Hidayat; Zulhendri Zulhendri; Sriyani Sriyani (Universitas Pahlawan Tuanku Tambusai, 2021)
Learning in the new normal era during the Corona Virus Disease 2019 (COVID-19) pandemic requires teachers to be more innovative and creative in preparing for learning. This activity is carried out in helping teachers to provide quality new normal education so that the learning objectives are achieved properly. The approach presented is participatory action research (PAR) with activity partners at Madrasah Aliyah Negeri (MAN) 1 Kampar. The activity is carried out in three stages, namely problem identification, activity implementation and activity evaluation. The activity was attended by 20 teachers, and the material provided included blended learning using the flipped classroom method. The result of this activity is the teacher's ability to understand the implementation of the flipped classroom model that is depicted during the simulation after the training is carried out. The indicators of the success of this community service implementation are activities carried out according to plan, as well as positive responses from participants.